IMPLEMENTASI ALGORITMA A-STAR DALAM MENENTUKAN RUTE PENGEJARAN OPTIMAL PADA PERMAINAN MEMBASMI NARKOBA - Lukas Tommy; Yohanes Setiawan Japriadi; Syachriza Hilmaida Habibur (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Drugs have several negative effects such as dependence, brain and nerve damage, to death if abused. Socialization about the dangers of drug abuse in society by police is still carried out conventionally so that it is less effective especially during the Covid-19 pandemic like today. In this research, an Android game that can convey material on the dangers of drugs in an interesting, interactive, and effective way will be proposed. In the proposed game, an artificial intelligence will be applied to the enemies in order to pursue player through optimal route. One of the algorithms for determining the closest route from the initial location to the destination is A-Star. A-Star algorithm utilize heuristics in evaluating nodes on a grid-shaped map so that its computation time is shorter than Dijkstra's. Based on the analysis that has been carried out, it is known that the overall performance of A-Star algorithm is good where the seven enemies in game can pursue player in real-time through optimal route. The enemies, however, are unable to cooperate in surround player and tend to gather at one point through the same route so that the effectiveness of the pursuit is not maximized. The proposed game can also convey material about the types of drugs and their negative impacts in an interesting, interactive, and effective manner through with gamepedia menu as well as the enemy characters displayed throughout the game.